The Role of Antibiotics in Endoscopic Transmural Drainage of Post-Inflammatory Pancreatic and Peripancreatic Fluid Collections - Jagielski, Mateusz; Kupczyk, Wojciech; Piątkowski, Jacek; Jackowski, Marek (Frontiers in Cellular and Infection Microbiology, 2022)
Background Although endoscopic treatment of symptomatic post-inflammatory pancreatic and peripancreatic fluid collections (PPPFCs) is an established treatment method, some aspects of endotherapy and periprocedural management remain controversial. The role of antibiotics is one of the most controversial issues in interventional endoscopic management of local complications of pancreatitis. Methods This study was a randomized, non-inferiority, placebo-controlled, and double-blinded clinical trial to investigate the role of antibiotic prophylaxis in endoscopic transmural drainage in patients with symptomatic non-infected PPPFCs and assess the influence of antibiotic treatment on the results of endotherapy in patients with symptomatic infected PPPFCs. This trial included 62 patients treated endoscopically for PPPFCs in 2020 at our medical center. Patients were divided into two groups; group 1 comprised patients who had received empirical intravenous antibiotic therapy during endotherapy and group 2 comprised patients who did not receive antibiotic therapy during endoscopic drainage of PPPFCs. The end points were clinical success and long-term success of endoscopic treatment. Results Thirty-one patients were included in group 1 (walled-off pancreatic necrosis [WOPN, 51.6%; pseudocyst, 48.4%) and 31 patients in group 2 (WOPN, 58.1%; pseudocyst, 41.9%) (p=0.6098/nonsignificant statistical [NS]). Infection with PPPFCs was observed in 15/31 (48.39%) patients in group 1 and in 15/31 (48.39%) patients in group 2 (p=1.0/NS). The average time of active (with flushing through nasocystic drainage) drainage in group 1 was 13.0 (6 – 21) days and was 14.0 (7 – 25) days in group 2 (p=0.405/NS). The average total number endoscopic procedures on one patient was 3.3 (2 – 5) in group 1 and 3.4 (2 – 7) in group 2 (p=0.899/NS). Clinical success of PPPFCs was observed in 29/31 (93.5%) patients from group 1 and in 30/31 (96.8%) patients from group 2 (p=0.5540/NS). Complications of endotherapy were noted in 8/31 (25.8%) patients in group 1 and in 10/31 (32.3%) patients in group 2 (p=0.576/NS). Long-term success in group 1 and 2 was reported in 26/31 (83.9%) and 24/31 (77.4%) patients, respectively (p=0.520/NS). Conclusions The effective endoscopic drainage of sterile PPPFCs requires no preventive or prophylactic use of antibiotics. In infected PPPFCs, antibiotic therapy is not required for effective endoscopic transmural drainage.